The Assessment of Efficiency of Information Technologies Launching by Belarusian Business - A. V. Aginskaya; R. I. Marozau (Цифровая трансформация)
The main purpose of the article is to analyze the effect of the information technologies (IT) usage by Belarusian SMEs based on a sample survey of CEOs from 424 entities. The study showed that, in general, business processes automation brings positive effects; in particular, IT can improve interaction with suppliers, contractors and banks, as well as, in general, increases the enterprise competitiveness. The correlation results demonstrate how organizational factors are associated with the management's assessment of the IT impact both on general performance and on specific business processes. In the conclusion, the policy implications on stimulating the IT usage by Belarusian enterprises are presented.